Grenada : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Requests for Waivers and Modification of Quantitative Performance Criteria, and Financing Assurances Review; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Grenada. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper presents key findings of the Second Review for Grenada under the Poverty Reduction and Growth Facility (PRGF). Grenada's economic outlook has deteriorated somewhat, mainly reflecting the global financial turmoil and slowing global growth. Financial turmoil and the global economic slowdown are expected to slow tourism demand, FDI, and remittances, and could also negatively affect grants from some donors. The authorities are moving forward with a policy framework that provides for needed fiscal consolidation, addresses financial sector vulnerabilities, and reinvigorates the structural agenda.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet